TRUVADA: PROMOTING GAY PROMISCUITY OR ENDING THE HIV STIGMA? THE NEW YORK TIMES AND THE ADVOCATE AS FACILITATORS OF ONLINE DEBATES AROUND THE HIV PREVENTION PILL - Hackl, Andrea; Newman, Todd (AoIR Selected Papers of Internet Research, 2015)
In Communication scholarship, a number of studies address the role of online commenting platforms in allowing for debates on issues of public interest. In consideration of the important roles of underlying policy designs in shaping these debates, the current study assessed differences in online reader perceptions around the HIV prevention pill Truvada on the mainstream news platform, The New York Times, and the LGBT platform, The Advocate. The study’s results suggest that readers of both platforms were primarily concerned with the medical and scientific implications of Truvada. Moreover, readers of The New York Times were significantly more likely to frame the issue in terms of political/economic concerns, while readers of The Advocate were significantly more likely to frame the issue in terms of medical/science concerns. The paper’s conclusion will discuss implications of these results for future research and preventative health strategies.